EB (Epstein-Barr) membrane composite adhesive and preparation method thereof
By adding specific materials to EB film composite glue and using electron beam curing technology, the problem of degradation of composite glue performance at high temperatures and ultraviolet light is solved, and higher heat resistance and ultraviolet resistance are achieved, extending service life and improving The barrier effect and aesthetics are achieved.
Patent Information
- Application Number
- CN202411533098.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-02-18
AI Technical Summary
The existing EB film composite glue has deteriorated performance in high temperature environments and ultraviolet exposure, is prone to deformation, weakened barrier effect, and is temperature sensitive.
Made of materials such as polyurethane acrylate resin, epoxy acrylate, acrylate monomer, crosslinking agent, curing agent, plasticizer, stabilizer, defoaming agent, leveling agent, benzophenone, titanium dioxide and aluminum foil. The EB film composite glue was formed and processed by electron beam curing technology.
It improves the high temperature resistance and ultraviolet resistance of composite glue, extends its service life, maintains its original performance, and improves the overall barrier effect and aesthetics.
Smart Images

Figure CN119463784A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer material preparation, in particular to an EB film composite adhesive and a preparation method thereof. Background Art
[0002] EB composite glue, that is, composite glue using electron beam curing technology, is a high-performance, environmentally friendly adhesive. EB curing technology directly acts on the molecules in the glue through high-energy electron beams, triggering its rapid cross-linking and curing, thereby achieving firm bonding of the material. This technology has a series of unique advantages, making EB composite glue widely used in many fields. No volatile organic compounds are produced during the EB curing process, which meets modern environmental protection requirements, is conducive to improving the production environment and protecting the ecology. EB curing speed is extremely fast, usually only a few seconds to a few minutes to complete the curing process, greatly improving production efficiency. EB curing is not limited by the color, light transmittance or thickness of the material and can be applied to Used for various complex composite structures and materials, the preparation process of EB film composite adhesive in the prior art is complicated. The composite film has high requirements on temperature during manufacturing and use. When encountering a high temperature environment, the film material may be deformed, thereby reducing its barrier effect and overall performance. This sensitivity to temperature limits the application of EB composite film under certain extreme temperature conditions, and EB composite film is easily affected by ultraviolet rays and sunlight. Long-term exposure to sunlight may cause the transparency of the film material to decrease, the color to darken, etc., which will not only affect the aesthetics of the product, but may also have an adverse effect on the quality of the product. In this regard, we proposed an EB film composite adhesive and a preparation method thereof. Summary of the invention
[0003] In order to solve the above technical problems, an EB film composite adhesive and a preparation method thereof are provided. This technical solution solves the above problems.
[0004] To achieve the above purpose, the technical solution adopted by the present invention is: an EB film composite adhesive, which is made of the following materials: 10-500 parts of polyurethane acrylate resin, 50-780 parts of epoxy acrylate, 1-450 parts of acrylate monomer, 10-300 parts of cross-linking agent, 20-340 parts of curing agent, 30-300 parts of plasticizer, 1-150 parts of stabilizer, 5-350 parts of defoaming agent, 25-460 parts of leveling agent, 20-78 parts of benzophenone, 25-355 parts of titanium dioxide and 1-455 parts of aluminum foil.
[0005] Preferably, the EB film composite adhesive is made of the following materials: 150-250 parts of polyurethane acrylate resin, 200-250 parts of epoxy acrylate, 200-370 parts of acrylate monomer, 150-250 parts of cross-linking agent, 80-150 parts of curing agent, 90-120 parts of plasticizer, 40-100 parts of stabilizer, 40-90 parts of defoaming agent, 30-60 parts of leveling agent, 20-40 parts of benzophenone, 30-40 parts of titanium dioxide and 60-100 parts of aluminum foil.
[0006] Preferably, the EB film composite adhesive is made of the following materials: 220 parts of polyurethane acrylate resin, 220 parts of epoxy acrylate, 350 parts of acrylate monomer, 210 parts of cross-linking agent, 120 parts of curing agent, 110 parts of plasticizer, 90 parts of stabilizer, 88 parts of defoaming agent, 56 parts of leveling agent, 32 parts of benzophenone, 37 parts of titanium dioxide and 90 parts of aluminum foil.
[0007] Preferably, the EB film composite adhesive is made of the following materials: 190 parts of polyurethane acrylate resin, 190 parts of epoxy acrylate, 210 parts of acrylate monomer, 180 parts of cross-linking agent, 90 parts of curing agent, 110 parts of plasticizer, 50 parts of stabilizer, 57 parts of defoaming agent, 35 parts of leveling agent, 25 parts of benzophenone, 35 parts of titanium dioxide and 78 parts of aluminum foil.
[0008] The parts of each raw material in the EB film composite adhesive of the present invention are parts by mass or parts by weight.
[0009] The aluminum foil used in the present invention is aluminum foil powder particles that have been crushed and ground, and filtered through a 16-mesh filter screen, with a particle size of about 1 mm, especially 0.9-1.0 mm.
[0010] Preferably, the ratio of polyurethane acrylate resin to epoxy acrylate is 1:1. We have found that the best product can be obtained under this ratio.
[0011] Preferably, the crosslinking agent includes organic peroxides, amines, inorganic acid esters and aldehydes, the curing agent includes aliphatic amines, aromatic amines, amide amines, latent curing amines and urea substitutes, the plasticizer includes phthalate esters, fatty acid esters, polyesters and epoxy esters, the stabilizer includes lead salt stabilizers, organotin stabilizers, rare earth stabilizers, organic auxiliary stabilizers and hydrotalcite stabilizers, the defoamer includes emulsion type, dispersion type, oil type and paste type, and the leveling agent includes silicone leveling agent and acrylate leveling agent.
[0012] The benzophenone in the present invention can be prepared by a phenol method, wherein phenol and polyphosphoric acid are added to a reaction pot, heated and subjected to a condensation reaction, and a crude product is obtained after cooling, and the crude product is finely treated. Titanium dioxide can be prepared based on a sulfuric acid method, and is obtained through acidolysis, purification, hydrolysis and roasting. Conventional aluminum foil is used for aluminum foil.
[0013] A method for preparing an EB film composite adhesive, the preparation steps are:
[0014] S1. Prepare the following materials: 10-500 parts of polyurethane acrylate resin, 50-780 parts of epoxy acrylate, 1-450 parts of acrylate monomer, 10-300 parts of cross-linking agent, 20-340 parts of curing agent, 30-300 parts of plasticizer, 1-150 parts of stabilizer, 5-350 parts of defoaming agent, 25-460 parts of leveling agent, 20-78 parts of benzophenone, 25-355 parts of titanium dioxide and 1-455 parts of aluminum foil;
[0015] S2, material pretreatment, purifying the acrylate monomer, placing the aluminum foil in a pickling agent for pickling treatment to remove oil stains, oxides and other impurities;
[0016] S3, crushing the aluminum foil, and grinding it to obtain aluminum foil powder for later use;
[0017] S4, weighing the basic materials according to the proportion, putting them into the reactor, performing preliminary mixing, and adjusting the working parameters of the reactor;
[0018] S5, waiting for the reaction to be completed, modulating the composite glue obtained by the preliminary reaction according to the performance of the product, first adding the additives and stirring, and during the stirring process, adding the aluminum foil powder and titanium dioxide again and stirring;
[0019] S6. Use electron beam technology to cure the composite adhesive, and cut and shape the cured composite adhesive to obtain the required shape;
[0020] S7. Conduct quality inspection on the processed EB film composite adhesive and package it after it passes the inspection.
[0021] Preferably, in step S2, the purification of the acrylate monomer is performed based on extraction, an extractant is selected, the acrylate monomer and the extractant are mixed and stirred to form a two-phase system, the system is allowed to stand and wait, the two layers are separated, the extractant is removed by distillation, and the obtained acrylate monomer is dried to obtain a purified acrylate monomer.
[0022] Preferably, in the aluminum foil crushing step in step S3, the pickled aluminum foil is placed in a crusher for preliminary crushing treatment, and after the preliminary crushing, secondary crushing is performed to obtain aluminum foil particles with smaller particle size, and finally the aluminum foil particles are placed in a grinder for continuous grinding treatment, filtered through a 16-mesh filter to remove large particle impurities, and obtain aluminum foil powder.
[0023] Preferably, in step S4, the stirring speed of the reactor is 1200r / min, and the stirring time is 2h; in step S5, after stirring for 60min, a cross-linking agent and a plasticizer are added into the reactor and stirred continuously; after stirring for 70min, a stabilizer and a defoaming agent are added into the reactor and stirred continuously; after stirring for 90min, a leveling agent is added into the reactor and stirred continuously; after stirring for 100min, aluminum foil powder and titanium dioxide are added again and stirred; finally, a curing agent is added and stirred.
[0024] Preferably, in step S6, the energy, beam density, and scanning speed parameters of the electron beam accelerator are pre-set, the electron accelerator is started, a high-energy electron beam is generated, and the path and energy of the electron beam are controlled so that it irradiates the surface of the composite glue. Under the irradiation of the electron beam, the molecular chains in the composite glue will undergo a cross-linking reaction to form a stable network structure, thereby achieving curing.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] The EB film composite adhesive proposed in the present invention is prepared by adding benzophenone, titanium dioxide and aluminum foil materials inside the basic material. Benzophenone, as an ultraviolet absorber, absorbs external ultraviolet rays inside the composite adhesive, titanium dioxide can reflect ultraviolet rays and reduce the damage of ultraviolet rays to the material, and the addition of aluminum foil can improve the high temperature resistance of the composite adhesive, better expand the application occasions of the composite adhesive, improve the overall barrier effect of the prepared composite adhesive material, make it less susceptible to the influence of ultraviolet sunlight, and improve the aesthetics. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The present invention is a flow chart of the steps for preparing the EB film composite adhesive. DETAILED DESCRIPTION
[0028] The following description is used to disclose the present invention so that those skilled in the art can implement the present invention. The preferred embodiments described below are only examples, and those skilled in the art may think of other obvious variations.
[0029] The EB film composite adhesive is made of the following materials: 10-500 parts of polyurethane acrylate resin, 50-780 parts of epoxy acrylate, 1-450 parts of acrylate monomer, 10-300 parts of crosslinking agent, 20-340 parts of curing agent, 30-300 parts of plasticizer, 1-150 parts of stabilizer, 5-350 parts of defoaming agent, 25-460 parts of leveling agent, 20-78 parts of benzophenone, 25-355 parts of titanium dioxide and 1-455 parts of aluminum foil.
[0030] By adding plasticizers, the present application can reduce the glass transition temperature of the polymer, so that the material can show good flexibility at a lower temperature, and improve the flexibility and plasticity of the product. The plasticizer can also reduce the viscosity of the polymer, improve its processability, and make the production process smoother. By adding stabilizers, the oxidation reaction in the EB film can be effectively inhibited or delayed to prevent it from being damaged by oxidation, which is very important for extending the service life of the EB film and maintaining its original performance. The addition of stabilizers can improve the thermal stability of the EB film and prevent it from decomposing or deteriorating at high temperatures, thereby maintaining its good physical and chemical properties. The addition of titanium dioxide can maintain good performance in harsh environments such as high temperature, high humidity and strong light, helping to improve the overall stability and durability of the EB film, so that it can maintain excellent performance in various application environments.
[0031] Benzophenone and benzophenone and its derivatives, such as benzophenone-3, also known as oxybenzone, are common UV absorbers that can absorb UV rays, thereby protecting the skin from UV damage. Titanium dioxide is a physical sunscreen whose main component is titanium dioxide. Titanium dioxide can reflect UV rays, thereby reducing UV damage to the skin and playing a role in sun protection. Aluminum foil is also an excellent "insulator" of heat and can be used to make thermal insulation materials. It absorbs external UV rays inside the composite adhesive. Titanium dioxide can reflect UV rays and reduce UV damage to materials. The addition of aluminum foil can improve the high temperature resistance of the composite adhesive, better expand the application occasions of the composite adhesive, and enhance the overall barrier effect of the prepared composite adhesive material, making it less susceptible to the influence of ultraviolet sunlight and improving the aesthetics.
[0032] The optimal ratio of polyurethane acrylate resin to epoxy acrylate is 1:1.
[0033] The combination of the polyurethane acrylate resin and epoxy acrylate in the present application can give the product excellent physical properties, such as high strength, high toughness, wear resistance, and chemical corrosion resistance. The mixed use of the two resins helps to improve the thermal stability of the product, so that it can still maintain stable performance in a high temperature environment. The polyurethane acrylate resin has good weather resistance. After combining with epoxy acrylate, it can further improve the weather resistance of the product and extend its service life.
[0034] Cross-linking agents include organic peroxides, amines, inorganic acid esters and aldehydes; curing agents include aliphatic amines, aromatic amines, amide amines, latent curing amines and urea substitutes; plasticizers include phthalates, fatty acid esters, polyesters and epoxy esters; stabilizers include lead salt stabilizers, organotin stabilizers, rare earth stabilizers, organic auxiliary stabilizers and hydrotalcite stabilizers; defoamers include emulsion type, dispersion type, oil type and paste type; leveling agents include silicone leveling agents and acrylate leveling agents.
[0035] Benzophenone can be prepared by the phenol method, adding phenol and polyphosphoric acid into a reaction pot, heating and carrying out a condensation reaction, waiting for cooling to obtain a crude product, and then finely treating the crude product; titanium dioxide can be prepared based on the sulfuric acid method, and is obtained through acidolysis, purification, hydrolysis and roasting; aluminum foil can be prepared by melting aluminum ingots, continuously casting, rolling after continuous casting, and finally cutting into sheets of aluminum foil.
[0036] A method for preparing an EB film composite adhesive, the preparation steps are:
[0037] S1. Prepare the following materials: 10-500 parts of polyurethane acrylate resin, 50-780 parts of epoxy acrylate, 1-450 parts of acrylate monomer, 10-300 parts of cross-linking agent, 20-340 parts of curing agent, 30-300 parts of plasticizer, 1-150 parts of stabilizer, 5-350 parts of defoaming agent, 25-460 parts of leveling agent, 20-78 parts of benzophenone, 25-355 parts of titanium dioxide and 1-455 parts of aluminum foil;
[0038] S2, material pretreatment, purifying the acrylate monomer, placing the aluminum foil in a pickling agent for pickling treatment to remove oil stains, oxides and other impurities;
[0039] S3, crushing the aluminum foil, and grinding it to obtain aluminum foil powder for later use;
[0040] S4, weighing the basic materials according to the proportion, putting them into the reactor, performing preliminary mixing, and adjusting the working parameters of the reactor;
[0041] S5, waiting for the reaction to be completed, modulating the composite glue obtained by the preliminary reaction according to the performance of the product, first adding the additives and stirring, and during the stirring process, adding the aluminum foil powder and titanium dioxide again and stirring;
[0042] S6. Use electron beam technology to cure the composite adhesive, and cut and shape the cured composite adhesive to obtain the required shape;
[0043] S7. Conduct quality inspection on the processed EB film composite adhesive and package it after it passes the inspection.
[0044] In step S2, the acrylate monomer may be purified first. Purification is performed based on extraction, an extractant is selected, the acrylate monomer and the extractant are mixed and stirred to form a two-phase system, the system is left to stand, the two layers are separated, the extractant is removed by distillation, and the obtained acrylate monomer is dried to obtain a purified acrylate monomer.
[0045] The impurity content of the acrylate monomer after extraction and purification in the present application is significantly reduced, which helps to improve the efficiency of subsequent polymerization reactions and reduce the occurrence of side reactions, thereby preparing polymer products with better performance and more stable quality. The impurities that affect the appearance are removed, making the acrylate monomer present a purer and more transparent appearance. The extraction process is simple and can be automatically controlled, providing high production efficiency and stability.
[0046] In the aluminum foil crushing step in step S3, the pickled aluminum foil is placed in a crusher for preliminary crushing, and after the preliminary crushing, secondary crushing is performed to obtain aluminum foil particles with smaller particle size, and finally the aluminum foil particles are placed in a grinder for continuous grinding, filtered through a 16-mesh filter to remove large particles of impurities, and aluminum foil powder particles are obtained with a particle size of about 1 mm. Compared with pure aluminum powder, the use of aluminum foil powder particles in this application can make the composite adhesive have better performance in terms of UV resistance and heat resistance.
[0047] The present application can provide convenience for subsequent processing and reduce processing time by crushing the aluminum foil after pickling, so as to obtain aluminum foil particles with fine particle size, and then obtain aluminum foil powder after grinding. The addition of materials can effectively improve the high temperature resistance of the prepared composite adhesive.
[0048] In step S4, the stirring speed of the reactor is 1200r / min, and the stirring time is 2h; in step S5, after stirring for 60min, a cross-linking agent and a plasticizer are added into the reactor for continuous stirring; after stirring for 70min, a stabilizer and a defoaming agent are added into the reactor for continuous stirring; after stirring for 90min, a leveling agent is added into the reactor for continuous stirring; after stirring for 100min, aluminum foil powder and titanium dioxide are added again for stirring, and finally a curing agent is added for stirring.
[0049] In step S6, the energy, beam density, and scanning speed parameters of the electron beam accelerator are pre-set, the electron accelerator is started, a high-energy electron beam is generated, and the path and energy of the electron beam are controlled so that it irradiates the surface of the composite glue. Under the irradiation of the electron beam, the molecular chains in the composite glue will undergo a cross-linking reaction to form a stable network structure, thereby achieving curing.
[0050] Example 1
[0051] A method for preparing an EB film composite adhesive, the preparation steps are:
[0052] S1. Prepare the following materials: 220 parts of polyurethane acrylate resin, 220 parts of epoxy acrylate, 350 parts of acrylate monomer, 180 parts of cross-linking agent, 120 parts of curing agent, 110 parts of plasticizer, 90 parts of stabilizer, 88 parts of defoamer, 56 parts of leveling agent, 32 parts of benzophenone, 37 parts of titanium dioxide and 90 parts of aluminum foil;
[0053] S2, material pretreatment, purifying the acrylate monomer, placing the aluminum foil in a pickling agent for pickling treatment to remove oil stains, oxides and other impurities;
[0054] S3, crushing the aluminum foil, and grinding it to obtain aluminum foil powder for later use;
[0055] S4, weighing the basic materials according to the proportion, putting them into the reactor, performing preliminary mixing, and adjusting the working parameters of the reactor;
[0056] S5, waiting for the reaction to be completed, modulating the composite glue obtained by the preliminary reaction according to the performance of the product, first adding the additives and stirring, and during the stirring process, adding the aluminum foil powder and titanium dioxide again and stirring;
[0057] S6. Use electron beam technology to cure the composite adhesive, and cut and shape the cured composite adhesive to obtain the required shape;
[0058] S7. Conduct quality inspection on the processed EB film composite adhesive and package it after it passes the inspection.
[0059] Example 2
[0060] A method for preparing an EB film composite adhesive, the preparation steps are:
[0061] S1. Prepare the following materials: 190 parts of polyurethane acrylate resin, 190 parts of epoxy acrylate, 210 parts of acrylate monomer, 180 parts of cross-linking agent, 90 parts of curing agent, 110 parts of plasticizer, 50 parts of stabilizer, 57 parts of defoaming agent, 35 parts of leveling agent, 25 parts of benzophenone, 35 parts of titanium dioxide and 78 parts of aluminum foil;
[0062] S2, material pretreatment, purifying the acrylate monomer, placing the aluminum foil in a pickling agent for pickling treatment to remove oil stains, oxides and other impurities;
[0063] S3, crushing the aluminum foil, and grinding it after crushing to obtain aluminum foil powder for standby use;
[0064] S4, weighing the basic materials according to the proportion, putting them into the reactor, performing preliminary mixing, and adjusting the working parameters of the reactor;
[0065] S5, waiting for the reaction to be completed, modulating the composite glue obtained by the preliminary reaction according to the performance of the product, first adding the additives and stirring, and during the stirring process, adding the aluminum foil powder and titanium dioxide again and stirring;
[0066] S6. Use electron beam technology to cure the composite adhesive, and cut and shape the cured composite adhesive to obtain the required shape;
[0067] S7. Conduct quality inspection on the processed EB film composite adhesive and package it after it passes the inspection.
[0068] Example 3
[0069] A method for preparing an EB film composite adhesive, the preparation steps are:
[0070] S1. Prepare the following materials: 200 parts of polyurethane acrylate resin, 120 parts of epoxy acrylate, 190 parts of acrylate monomer, 210 parts of cross-linking agent, 90 parts of curing agent, 230 parts of plasticizer, 50 parts of stabilizer, 57 parts of defoaming agent, 35 parts of leveling agent, 25 parts of benzophenone, 185 parts of titanium dioxide and 78 parts of aluminum foil;
[0071] S2, material pretreatment, purifying the acrylate monomer, placing the aluminum foil in a pickling agent for pickling treatment to remove oil stains, oxides and other impurities;
[0072] S3, crushing the aluminum foil, and grinding it after crushing to obtain aluminum foil powder for standby use;
[0073] S4, weighing the basic materials according to the proportion, putting them into the reactor, performing preliminary mixing, and adjusting the working parameters of the reactor;
[0074] S5, waiting for the reaction to be completed, modulating the composite glue obtained by the preliminary reaction according to the performance of the product, first adding the additives and stirring, and during the stirring process, adding the aluminum foil powder and titanium dioxide again and stirring;
[0075] S6. Use electron beam technology to cure the composite adhesive, and cut and shape the cured composite adhesive to obtain the required shape;
[0076] S7. Conduct quality inspection on the processed EB film composite adhesive and package it after it passes the inspection.
[0077] Comparative Example 1
[0078] The preparation steps of EB film composite adhesive are as follows:
[0079] A1. Weigh all materials except aluminum foil in Example 2, and accurately weigh the required raw materials, including resin, monomer, and additives according to the formula requirements;
[0080] A2. Mix the raw materials. Mix the weighed raw materials at 20℃~80℃ to ensure that all components are in full contact;
[0081] A3. Use a stirring device to stir the mixed raw materials at high speed to make the components evenly dispersed. The stirring speed is between 1000 and 1200 rpm.
[0082] A4. After the raw materials are evenly mixed, add additives such as defoamer and leveling agent, and continue to stir evenly to obtain the required EB composite glue;
[0083] A5. Curing: The substrate coated with EB composite glue is cured by electron beam curing technology. During the curing process, the high-energy radiation of the electron beam causes the monomer and resin in the glue to undergo a cross-linking reaction to form a stable network structure.
[0084] A6. Die-cutting: For finished products that require specific shapes, the cured composite film may need to be die-cut. The finished products must be quality inspected to ensure that they meet relevant standards and requirements before being packaged and stored.
[0085] Comparative Example 2
[0086] The method of Example 1 is adopted, wherein the aluminum foil is replaced by aluminum powder, and step S3 is removed.
[0087] Table 1 below shows the properties of the EB film composite adhesives prepared in different embodiments and comparative examples.
[0088]
[0089] Table 1
[0090] UV resistance testing
[0091] Prepare samples prepared in the embodiments and comparative examples for testing;
[0092] Turn on the power of the UV protection tester to preheat it, place the EB film composite adhesive sample on the bracket provided by the tester, turn on the UV lamp, and irradiate it on the sample surface for 15-30s;
[0093] After stopping the UV lamp irradiation, wait for the test instrument to display the reading and record it accurately;
[0094] Repeat the above test steps multiple times to calculate the average value or perform statistical analysis.
[0095] Heat resistance test
[0096] Prepare samples prepared in the embodiments and comparative examples for testing;
[0097] Place the EB film composite adhesive sample on the sample rack of a high-temperature oven or other testing equipment, ensuring that the sample is at an appropriate distance from the heat source to avoid local overheating;
[0098] Set the temperature of the high temperature oven or test equipment. The temperature setting should be accurate and remain stable during the test;
[0099] Start the test equipment and begin heating. During the test, pay close attention to changes in the sample, such as color, shape, and size;
[0100] During the test, the test data such as temperature, time, weight change and deformation degree of the sample are recorded regularly to obtain the results.
[0101] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions only describe the principles of the present invention. The present invention may be subject to various changes and improvements without departing from the spirit and scope of the present invention. These changes and improvements fall within the scope of the present invention. The scope of protection claimed by the present invention is defined by the attached claims and their equivalents.
Claims
1. An EB film composite adhesive, characterized in that: The EB film composite adhesive is made of the following materials: 10-500 parts of polyurethane acrylate resin, 50-780 parts of epoxy acrylate, 1-450 parts of acrylate monomer, 10-300 parts of cross-linking agent, 20-340 parts of curing agent, 30-300 parts of plasticizer, 1-150 parts of stabilizer, 5-350 parts of defoaming agent, 25-460 parts of leveling agent, 20-78 parts of benzophenone, 25-355 parts of titanium dioxide and 1-455 parts of aluminum foil.
2. The EB film composite adhesive according to claim 1, characterized in that: EB film composite adhesive is made of the following materials: 150-250 parts of polyurethane acrylate resin, 200-250 parts of epoxy acrylate, 200-370 parts of acrylate monomer, 150-250 parts of cross-linking agent, 80-150 parts of curing agent, 90-120 parts of plasticizer, 40-100 parts of stabilizer, 40-90 parts of defoaming agent, 30-60 parts of leveling agent, 20-40 parts of benzophenone, 30-40 parts of titanium dioxide and 60-100 parts of aluminum foil.
3. The EB film composite adhesive according to claim 1, characterized in that: The EB film composite adhesive is made of the following materials: 220 parts of polyurethane acrylate resin, 220 parts of epoxy acrylate, 350 parts of acrylate monomer, 180 parts of cross-linking agent, 120 parts of curing agent, 110 parts of plasticizer, 90 parts of stabilizer, 88 parts of defoaming agent, 56 parts of leveling agent, 32 parts of benzophenone, 37 parts of titanium dioxide and 90 parts of aluminum foil.
4. The EB film composite adhesive according to claim 1, characterized in that: The EB film composite adhesive is made of the following materials: 190 parts of polyurethane acrylate resin, 190 parts of epoxy acrylate, 210 parts of acrylate monomer, 180 parts of cross-linking agent, 90 parts of curing agent, 110 parts of plasticizer, 50 parts of stabilizer, 57 parts of defoaming agent, 35 parts of leveling agent, 25 parts of benzophenone, 35 parts of titanium dioxide and 78 parts of aluminum foil.
5. The EB film composite adhesive according to claim 1, characterized in that: The ratio of polyurethane acrylate resin to epoxy acrylate is 1:1; crosslinking agents include organic peroxides, amines, inorganic acid esters and aldehydes; curing agents include aliphatic amines, aromatic amines, amide amines, latent curing amines and urea substitutes; plasticizers include phthalates, fatty acid esters, polyesters and epoxy esters; stabilizers include lead salt stabilizers, organic tin stabilizers, rare earth stabilizers, organic auxiliary stabilizers and hydrotalcite stabilizers; defoamers include emulsion type, dispersion type, oil type and paste type; leveling agents include silicone leveling agents and acrylate leveling agents.
6. A method for preparing an EB film composite adhesive, characterized in that: The preparation steps are: S1. Prepare the following materials: 10-500 parts of polyurethane acrylate resin, 50-780 parts of epoxy acrylate, 1-450 parts of acrylate monomer, 10-300 parts of cross-linking agent, 20-340 parts of curing agent, 30-300 parts of plasticizer, 1-150 parts of stabilizer, 5-350 parts of defoaming agent, 25-460 parts of leveling agent, 20-78 parts of benzophenone, 25-355 parts of titanium dioxide and 1-455 parts of aluminum foil; S2, material pretreatment, purifying the acrylate monomer, placing the aluminum foil in a pickling agent for pickling treatment to remove oil stains, oxides and other impurities; S3, crushing the aluminum foil, and grinding it to obtain aluminum foil powder for later use; S4, weighing the basic materials according to the proportion, putting them into the reactor, performing preliminary mixing, and adjusting the working parameters of the reactor; S5, waiting for the reaction to be completed, modulating the composite glue obtained by the preliminary reaction according to the performance of the product, first adding the additives and stirring, and during the stirring process, adding the aluminum foil powder and titanium dioxide again and stirring; S6. Use electron beam technology to cure the composite adhesive, and cut and shape the cured composite adhesive to obtain the required shape; S7. Conduct quality inspection on the processed EB film composite adhesive and package it after it passes the inspection.
7. The method for preparing the EB film composite adhesive according to claim 6, characterized in that: In step S2, the purification of the acrylate monomer is based on extraction. An extractant is selected, the acrylate monomer and the extractant are mixed and stirred to form a two-phase system, the system is allowed to stand and wait, the two layers are separated, the extractant is removed by distillation, and the obtained acrylate monomer is dried to obtain a purified acrylate monomer.
8. The method for preparing the EB film composite adhesive according to claim 6, characterized in that: In the aluminum foil crushing step in step S3, the pickled aluminum foil is placed in a crusher for preliminary crushing treatment. After the preliminary crushing, secondary crushing is performed to obtain aluminum foil particles with smaller particle size. Finally, the aluminum foil particles are placed in a grinder for continuous grinding treatment, and filtered through a 16-mesh filter to remove large particle impurities to obtain aluminum foil powder particles.
9. The method for preparing the EB film composite adhesive according to claim 6, characterized in that: In step S4, the stirring speed of the reactor is 1200r / min, and the stirring time is 2h; in step S5, after stirring for 60min, a cross-linking agent and a plasticizer are added into the reactor for continuous stirring; after stirring for 70min, a stabilizer and a defoaming agent are added into the reactor for continuous stirring; after stirring for 90min, a leveling agent is added into the reactor for continuous stirring; after stirring for 100min, aluminum foil powder and titanium dioxide are added again for stirring, and finally a curing agent is added for stirring.
10. The method for preparing the EB film composite adhesive according to claim 6, characterized in that: In step S6, the energy, beam density, and scanning speed parameters of the electron beam accelerator are pre-set, the electron accelerator is started, a high-energy electron beam is generated, and the path and energy of the electron beam are controlled so that it irradiates the surface of the composite glue. Under the irradiation of the electron beam, the molecular chains in the composite glue undergo a cross-linking reaction to form a stable network structure, thereby achieving curing.